El cabildo eclesiástico de Lima bajo la Unión de Armas, 1639-1648 - Sato, Masaki (2015)
Historians have argued that the Peruvian church collaborated with the fiscal reform of the Spanish Monarchy under Philip IV. This article, however, revises this interpretation by examining how the cathedral chapter of Lima reacted against the Unión de Armas, the keystone of the reform. This research analyzes the disputes over enacting the reform through the opinions of the cathedral chapter and the viceroy marqués de Mancera, who had different points of view about how to collect the tithe on wine. Then, it examines one lawsuit between the tithe collector and the treasurer of the archdiocese. This allows us to see how a sector of the Church was involved in fiscal fraud and resisted the Crown reform.